Multi-scale simulations of apatite–collagen composites: from molecules to materials - Zahn, Dirk (Frontiers of Materials Science, 2017)
We review scale-bridging simulation studies for the exploration of atomicto-meso scale processes that account for the unique structure and mechanic properties of apatite-protein composites. As the atomic structure and composition of such complex biocomposites only partially is known, the first part (i) of our modelling studies is dedicated to realistic crystal nucleation scenarios of inorganic-organic composites. Starting from the association of single ions, recent insights range from the mechanisms of motif formation, ripening reactions and the self-organization of nanocrystals, including their interplay with growth-controlling molecular moieties. On this basis, (ii) reliable building rules for unprejudiced scale-up models can be derived to model bulk materials. This is exemplified for (enamel-like) apatite-protein composites, encompassing up to 106 atom models to provide a realistic account of the 10 nm length scale, whilst model coarsening is used to reach extgreekmm length scales. On this basis, a series of deformation and fracture simulation studies were performed and helped to rationalize biocomposite hardness, plasticity, toughness, self-healing and fracture mechanisms. Complementing experimental work, these modelling studies provide particularly detailed insights into the relation of hierarchical composite structure and favorable mechanical properties.
EAM Import::2019-03-12